h3/h-6

Simple and best practice solution for h3/h-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h3/h-6 equation:


D( h )

h = 0

h = 0

h = 0

h in (-oo:0) U (0:+oo)

(h^3)/h-6 = 0

1*h^2 = 6 // : 1

h^2 = 6

h^2 = 6 // ^ 1/2

abs(h) = 6^(1/2)

h = 6^(1/2) or h = -6^(1/2)

h in { 6^(1/2), -6^(1/2) }

See similar equations:

| 4x+14-6x+22=4 | | 3y^2-20y+15=0 | | -x+9=-5x+57 | | (-x+9i)(x-9i)=0 | | 5/(x-3)-6=12/(x-3) | | 7x+2=2x+1 | | 116=121-x | | 5-3/12 | | 3=-4(1)+b | | a^2+9=9 | | 39-4a=7+6(1-5a) | | 2/5h=28 | | Y^4+16y=-1 | | -6x-(-6)-7=-7x+7 | | (-x-9i)(x-9i)=0 | | -38=-18-9 | | F(x)=1n(x-2)-4 | | x(3)+9=27 | | X^2+3=5x(x+6) | | 4(3+m)=8(6m+7) | | (x+9i)(x-9i)=0 | | 4x+7=22-x | | 7z-1=z+22 | | 3v+2y=100 | | 6cosx=4sinx | | (-x-9i)(x+9i)=0 | | -5x-1=29+5x | | -4y+7x=-24 | | 7x-(3+4x)= | | 3a-15=-14 | | 3c+18=14 | | 3r^2+25r+8=0 |

Equations solver categories